2016
DOI: 10.1016/j.jcot.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-free, stem cell-based cartilage repair

Abstract: Various approaches to treat articular cartilage have been widely investigated due to its poor intrinsic healing capacity. Stem cell-based therapy could be a promising approach as an alternative to chondrocyte-based therapy and some of these therapies have been already applied in clinical condition. This review discusses the current development of stem cell-based therapies in cartilage repair, specifically focusing on scaffold-free approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…In this regard, human synovium‐derived stem cells (hSSCs) have been identified as a good cell source based on their superior potential for chondrogenesis and proliferation compared with other adult stem cells in vitro (Sakaguchi, Sekiya, Yagishita, & Muneta, ). We have been developing several strategies for cartilage repair using hSSCs in vivo (Shimomura et al, ; Yasui, Ando, et al, ) and, moreover, have shown successful formation of cartilage‐like tissue from hSSCs in vitro (Chijimatsu et al, ; Koizumi et al, ; Yasui, Chijimatsu, et al, ). Although it will be potential alternatives for ACI, the cost to induce chondrogenesis using growth factors is not a negligible issue for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, human synovium‐derived stem cells (hSSCs) have been identified as a good cell source based on their superior potential for chondrogenesis and proliferation compared with other adult stem cells in vitro (Sakaguchi, Sekiya, Yagishita, & Muneta, ). We have been developing several strategies for cartilage repair using hSSCs in vivo (Shimomura et al, ; Yasui, Ando, et al, ) and, moreover, have shown successful formation of cartilage‐like tissue from hSSCs in vitro (Chijimatsu et al, ; Koizumi et al, ; Yasui, Chijimatsu, et al, ). Although it will be potential alternatives for ACI, the cost to induce chondrogenesis using growth factors is not a negligible issue for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[28]. In addition, there are some comparable approaches which focus on the production of SFCCs [9,11,[29][30][31]. SFCCs revealed a cartilage-like phenotype detected by gene expression and histological analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most 3D culture systems involve a scaffold to provide the cells with a predetermined structure where their distinct effects on the cells are often not considered. Recent developments aim to establish scaffold-free tissue engineered cartilage mainly from human chondrocytes which could serve as a promising approach to cartilage repair in vivo, as well as an excellent in vitro model, since ECM formation and degradation can be evaluated without the interference of a scaffold [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Such autologous synovial MSCs were applied to cartilage injury 29. Currently, only one clinical study repairing chondral defect using scaffold-free three-dimensional tissue engineered construct, derived from human synovial MSCs, was completed in March 2015; but, the outcomes of the study were not reported 30,31. This may be considered to be evident that these naturally occurring MSCs may play an important role in meniscal healing and regeneration.…”
Section: Introductionmentioning
confidence: 99%